1996
DOI: 10.1271/bbb.60.1893
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Arphamenine A on Intestinal Dipeptide Transport

Abstract: Arphamenine A, an Arg-Phe analog without a peptide bond, has been reported to be a possible inhibitor of the peptide transporter [H. Daniel and S.A. Adibi, FASEB J., 8, 753 (1994)]. The present study demonstrated that arphamenine A is not a real inhibitor, but is a substrate for the transporter, being transported transepithelially under a proton gradient. The substrate specificity of the peptide transporter was wider than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 2 publications
0
11
1
Order By: Relevance
“…Demonstration that -AFA with 4 -10 CH 2 units in the backbone bind to PEPT1 and are transported in an electrogenic fashion clearly establishes that the presence of a peptide bond in a substrate is not a structural requirement. Although previous studies using modified peptides (25,26) demonstrated that the replacement of the peptide bond by a ketomethylene or thioxo function still retains the affinity of these dipeptide mimetics for interaction with PEPT1, our studies establish that the complete removal of the peptide bond as well as of the side chains is tolerated without a significant loss in affinity. The apparent affinities as determined for selected -AFA in the competition assays as well as by the influx of radiolabeled 6-AHA and electrophysiology are very similar to those of representative dipeptides or tripeptides.…”
Section: Recordings Of Substrate-induced Inward Currents and I-v Recontrasting
confidence: 55%
“…Demonstration that -AFA with 4 -10 CH 2 units in the backbone bind to PEPT1 and are transported in an electrogenic fashion clearly establishes that the presence of a peptide bond in a substrate is not a structural requirement. Although previous studies using modified peptides (25,26) demonstrated that the replacement of the peptide bond by a ketomethylene or thioxo function still retains the affinity of these dipeptide mimetics for interaction with PEPT1, our studies establish that the complete removal of the peptide bond as well as of the side chains is tolerated without a significant loss in affinity. The apparent affinities as determined for selected -AFA in the competition assays as well as by the influx of radiolabeled 6-AHA and electrophysiology are very similar to those of representative dipeptides or tripeptides.…”
Section: Recordings Of Substrate-induced Inward Currents and I-v Recontrasting
confidence: 55%
“…3). The presence of arphamenine A, which is also a substrate for the peptide transporter with a low Km value, 21) slightly reduced the basolateral concentration of ValPro-Pro, although the decrease in the ‰ux was not signiˆcant. These results suggest that the peptide transporter did not play a signiˆcant role in the transepithelial transport of Val-Pro-Pro in the Caco-2 cell monolayer.…”
Section: Contribution Of Transporter-mediated Transport To the Transementioning
confidence: 95%
“…Gly-Pro is a good substrate for the peptide transporter with a low Km value, 21) and is fairly resistant to brush border peptidases. Gly-Pro has therefore often been used to analyze the peptide transporter functions.…”
Section: Contribution Of Transporter-mediated Transport To the Transementioning
confidence: 99%
“…7 indicates the AP-to-BL flux of KVLPVP was not significantly influenced in the presence of Gly-Pro (10 mM). In addition, the presence of arphamenine A (10 mM), which is also a substrate for the peptide transporter, 29) had minimal effect on the BL concentration of KVLPVP (Fig. 7).…”
Section: Contribution Of the Peptide Transporter To The Transepithelimentioning
confidence: 97%